EU-China relations: through the narrative of China's media - Zhang, Dechun (Universitas Muhammadiyah Yogyakarta, 2021)
China is the second-biggest trading partner of the European Union, and the EU is the biggest trading partner of China. Hence, it is vital to find the media perception of the EU and the political ideology behind it. This article aims to examine China’s official media perception of the EU by systematically examine the previous study. This study finds that Chinese media frame EU as an economic and political partner in a positive way but try to avoid mentioning the contradiction and friction, the selective negative issues are mainly for propaganda and conform to Chinese government attitude. Hence, this study discusses that Chinese official media follow the narrative of the Chinese government and reflect the EU-China relationship from the Chinese government perspective.